2016
DOI: 10.1186/s12969-016-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Familial autoimmunity in the childhood arthritis and rheumatology research alliance registry

Abstract: Background: Clinically distinct autoimmune phenotypes share genetic susceptibility factors. We investigated the prevalence of familial autoimmunity among subjects with juvenile idiopathic arthritis (JIA), childhood systemic lupus erythematosus (cSLE) and juvenile dermatomyositis (JDM) in the CARRA Registry, the largest multicenter observational Registry for pediatric rheumatic disease. Methods: Children with JIA, cSLE and JDM enrolled in the CARRA Registry between May 2010 and May 2012 were investigated for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
2
11
1
1
Order By: Relevance
“…Pohjankoski et al [ 20 ] studied the presence of IDDM, CD, MS and chronic arthritis in 355 families of JIA patients showing an overall prevalence of 21.4%. The data of a large cohort of patients in the United States have recently been published [ 21 ] showing that the prevalence of autoimmunity is increased among the relatives of JIA subjects compared to those of JDM with a greater proportion of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Pohjankoski et al [ 20 ] studied the presence of IDDM, CD, MS and chronic arthritis in 355 families of JIA patients showing an overall prevalence of 21.4%. The data of a large cohort of patients in the United States have recently been published [ 21 ] showing that the prevalence of autoimmunity is increased among the relatives of JIA subjects compared to those of JDM with a greater proportion of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, other factors such as biomarkers could add value to the clinical variables 8 . A high aggregation of autoimmunity including familial JIA is observed among first‐ and second‐degree relatives of patients with JIA; however, the knowledge about this observation is limited 9‐12 . Of note, recently, familial JIA gained more attention, and might be associated with guarded outcome 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that have looked at the familial aggregation of autoimmunity in JIA patients and their relatives, and have focused on the association and the estimated risk of autoimmune diseases among individuals and their relatives. However, the impact of clustering of autoimmunity has not been adequately studied 9,16,17 . There are scarce data published on JIA long‐term outcome in JIA patients with relatives with autoimmune diseases 18 .…”
Section: Introductionmentioning
confidence: 99%
“… 31 A registry study also found that higher proportions of patients with JIA versus other autoimmune diseases had first-degree relatives with any autoimmune disease. 32 A study conducted in Italy found that ~50% of patients with JIA had at least one relative with an autoimmune disease and that there was a high incidence risk of new autoimmune diseases in patients with JIA; however, the study was not able to predict which patients would develop autoimmune diseases, what disease would occur and at what time the disease would develop. 14 …”
Section: Discussionmentioning
confidence: 99%